Marine Plastic Pollution: ASEAN Values and the Bottom-Up Role of Divers Clean Action - Sonopaa, Angelique Gabriella; Ismoyo, Petsy Jessy; Seba, Roberto O.C. (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study analyzes the role of Divers Clean Action (DCA) as an implementation of ASEAN Values in a bottom-up approach to tackling marine plastic pollution in Southeast Asia. Using Alexander Wendt's constructivism theory, this study shows how DCA utilizes values such as collectivism, social harmony, respect for cultural diversity, and gotong royong to build a pro-environment collective identity. Qualitative research methods were applied through in-depth interviews with a DCA representative and document analysis, revealing that an ASEAN Values-based approach can form a strong pro-environmental collective identity while addressing the weaknesses of the top-down approach previously relied upon by ASEAN. However, challenges such as resource constraints and cross-border coordination require more structured policy support from ASEAN. This research makes an important contribution to the literature on regional environmental governance by demonstrating the potential for integrating local values and community-based approaches in addressing complex environmental issues. The implications of these findings suggest the need for a more inclusive policy framework that can combine the strengths of bottom-up and top-down approaches for more effective management of marine plastic pollution in the ASEAN region.